Sulfidization of Au(111) from thioacetic acid: An experimental and theoretical study - Fischer, Jeison A. (2012)
We have studied the adsorption of thioacetic acid (TAAH) on Au(111) from solution deposition. The close proximity of the SH groups to CO groups makes this molecule very attractive for exploring the effect of the functional group on the stability of the S-C and S-Au bonds. Although thioacetic acid was supposed to decompose slowly in water by hydrolysis supplying hydrogen sulfide, this behavior is not expected in nonpolar solvents such as toluene or hexane. Therefore, we have used these solvents for TAAH selfassembly on the Au(111) surface. The characterization of the adsorbates has been done by electrochemical techniques, X-ray photoelectron spectroscopy (XPS), and scanning tunneling microscopy (STM). We have found that even in nonpolar solvents thioacetic acid decomposes to S. The results have been discussed on the basis that the adsorbed species suffer a cleavage on the Au surface, leaving the S attached to it. The dissociation is a spontaneous process that reaches the final state very fast once it is energetically favorable, as can be interpreted from DFT calculations. The thioacetic acid adsorption reveals the strong effect that produces a functional group and the key role of the S-H bond cleavage in the self-assembly process.